Interleukin-1β downregulates RBP4 secretion in human adipocytes. - Primoz Kotnik; Michaela Keuper; Martin Wabitsch; Pamela Fischer-Posovszky (PLoS ONE, 2013)
AIMS/HYPOTHESIS: The excessive accumulation of adipose tissue in the obese state is linked to an altered secretion profile of adipocytes, chronic low-grade inflammation and metabolic complications. RBP4 has been implicated in these alterations, especially insulin resistance. The aim of the present study was to determine if a local inflammatory micro-environment in adipose tissue regulates RBP4 expression and secretion. METHODS: Human SGBS and primary adipocytes cultured with conditioned media from human THP-1 macrophages were used as an in vitro model for adipose inflammation. Adipocytes were exposed to recombinant TNF-α, IL-1β, IL-6 or IL-8. In addition, coexpression of IL-1β and RBP4 was measured in adipose tissue samples from 18 healthy females. RBP4 expression was studied by quantitative PCR and ELISA. RESULTS: RBP4 mRNA expression and secretion was significantly reduced upon incubation with macrophage-conditioned media in SGBS adipocytes and human primary adipocytes. Out of several factors studied we identified IL-1β as a new factor regulating RBP4. IL-1β significantly downregulated RBP4 mRNA and secretion in a time- and dose-dependent manner. IL-1β mediated its inhibitory effects on RBP4 expression via IL-1 receptor and NF-κB, as incubation with the IL-1 receptor blocking antibody and the NF-κB inhibitors CAPE and SC-514 reversed its effect. Most interestingly, RBP4 mRNA was negatively correlated with IL-1β mRNA in subcutaneous adipose tissue. CONCLUSIONS: Adipose tissue inflammation as found in the obese state might lead to a downregulation in local RBP4 levels. IL-1β was identified as a major factor contributing to the decrease in RBP4. The increase in circulating RBP4 that often precedes the development of systemic insulin resistance is most likely unrelated to inflammatory processes in adipose tissue.